مواقع التواصل الاجتماعي ودورها في نشر الوعي الصحي اثناء جائحة كورونا الفاسبوك نموذجا دراسةميدانية على عينة من الطلبة بجامعة عمار ثليجي- الأغواط- - بوزيد كلثوم; مشيكل إبراهيم; أمينة اقنيني (My University, 2022)
انطلقت دراستنا من إشكالية هل ساهمت موقع التواصل الاجتماعي في نشر الوعي الصحي أثناء جائحة كورونا لدى الطلبة الجامعيين؟ وهدفت الى التعرف على مساهمة مواقع التواصل الاجتماعي في نشر الوعي الصحي أثناء جائحة كورونا لدى الطلبة الجامعيين. -التعرف على مساهمة الفاسبوك في رفع مستوى الصحي لدى الطالب الجامعي اثناء جائحة كورونا. وللوصول الى نتائج الدراسة وحل هذه الإشكالية تم الاعتماد على المنهج الوصفي التحليلي لدراسة الحالة والاعتماد على عينة الدراسة المكونة من 63 طالب وطالبة من كلية العلوم الاجتماعية. وتم الوصول الى النتائج التالية: طلبة كلية العلوم الاجتماعية بجامعة عمار ثليجي الاغواط لا يبحثون عن اخبار كورونا دائما الا في بعض الأحيان وهذا نظرا لنقص المعلومات من المصدر حول هذا الوباء. ان طلبة كلية العلوم الاجتماعية يتفاعلون مع المنشورات الصحية عبر مواقع التواصل الاجتماعي تختلف باختلاف المنشورات والمصادر طلبة كلية العلوم الاجتماعية بجامعة الاغواط يتفاعلون مع المنشورات الصحية عبر مواقع التواصل الاجتماعي المستوى الفهم تختلف لديهم اذا انن نجد ان هناك من لديهم درجة فهم كبيرة وهناك من لديهم درجة فهم متوسطة. ان تصفح مواقع التواصل الاجتماعي ساهمة في زيادة معارف المتصفحين عن كوفيد 19 من خلال أساليب العلاج وكيفية الوقائية منه. درجة الثقة لدى طلبة كلية العلوم الاجتماعية بجامعة الاغواط في المعلومات الصحية عبر مواقع التواصل الاجتماعي تختلف باختلاف المنشورات والمصادر المعتمد عليها فنسبة كبيرة من الطلبة فاقت 70% لهم ثقة كبيرة في المعلومات حول فيروس كورونا. Our study started from the problem of whether the social networking site contributed to spreading health awareness during the Corona pandemic among university students? It aimed to identify the contribution of social media to spreading health awareness during the Corona pandemic among university students. - Identifying the contribution of Facebook to raising the health level of university students during the Corona pandemic. In order to reach the results of the study and solve this problem, it was relied on the descriptive analytical approach to the case study and relied on the study sample consisting of 63 male and female students from the College of Social Sciences. The following results were obtained: Students of the Faculty of Social Sciences at Ammar Thaleji University, Laghouat, do not always look for Corona news, except sometimes, and this is due to the lack of information from the source about this epidemic. Students of the College of Social Sciences interact with health publications through social networking sites that vary according to publications and sources. Students of the Faculty of Social Sciences at the University of Laghouat interact with health publications through social networking sites. The level of understanding they have varies, if we find that there are those who have a great degree of understanding and there are those who have a medium degree of understanding. Browsing social networking sites has contributed to increasing the knowledge of surfers about Covid 19 through methods of treatment and how to prevent it. The degree of confidence among students of the Faculty of Social Sciences at the University of Laghouat in health information via social media sites varies according to the publications and sources relied upon, as a large percentage of students, more than 70%, have great confidence in information about the Corona virus.